Practice and Exploration of the Reform of the International Talent Cultivation Model in Higher Vocational Colleges from the Perspective of New Quality Productivity - Chen Yin; Ding Wen (Journal of Exploration of Vocational Education, 2025)
Abstract:In the context of globalization and rapid development of the knowledge economy, vocational colleges urgently need to establish a talent training model which is both in line with international standards and has local characteristics. Faced with the strategic demand for internationalization and the requirement for new quality productivity of innovative talents, this article starts from the perspective of new quality productivity and adopts qualitative research methods to explore the practical ways of reforming the international talent training mode in vocational colleges. Through literature review and case analysis, this article identifies the key elements of the international talent cultivation model, namely the construction of an international curriculum system, the internationalization of the teaching staff, the cultivation of cross-cultural competence, and international exchange and cooperation. Based on this, detailed reform strategies are formulated. On this basis, this article proposes a series of innovative measures, including establishing a curriculum system centered on ability output, implementing international teacher training programs, strengthening exchanges and cooperation with international universities, and promoting student exchange programs. These measures provide novel ideas and feasible operational plans for the international talent cultivation of vocational colleges, which have significant theoretical contributions and practical guidance significance, and help improve the quality and international competitiveness of vocational education.